Polish Companies Experiences in Commercialization of New Technologies - Gwarda-Gruszczyńska, Edyta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
In 2009–2012 the research on strategies and tactics of commercialization was done. The aim of this article is to present the research results. Main area covered here is the area of innovation market implementation, especially strategies of Polish companies in this field. Different factors that can have influence on commercialization strategies were identified and analyzed. The starting point for their identification was factor importance in the success or failure of the commercialization process. As the result characteristics of four main commercialization strategies were presented.